Manajemen Kebutuhan Ruang Parkir Sepeda Motor Sebagai Alternatif Penanganan Fasilitas Parkir Sepeda Motor di Kampus Universitas Muhammadiyah Magelang - Naufal Fikri Mubarok; M. Agung W; Albani Musyafa; Rizki Budi Utomo (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The need for adequate parking space is one of the main challenges for the Muhammadiyah University Magelang Campus along with the increasing number of student and staff vehicles. The current parking facilities are not able to accommodate the volume of vehicles, especially on days with high campus activity. This condition demands an effective parking management solution to optimize the use of available land and meet future parking needs. This research aims to analyze the management of parking space requirements on the Muhammadiyah University Magelang Campus as an alternative in handling parking facilities. This study uses systematic research methods, starting from reviewing previous research, problem identification, surveys, data collection from written references, to data processing and drawing conclusions. The analysis results show that the need for vehicle parking spaces on campus is greatest on Wednesdays, with a total requirement of 1,293 SRP, while the currently available parking capacity is only 839 SRP. This indicates that the existing parking capacity is not sufficient for the needs of vehicles parked on campus. Projections for the next five years show the need for parking spaces of 1,600 SRP in 2025, 1,468 SRP in 2026, 1,462 SRP in 2027, 1,383 SRP in 2028, and 1,348 SRP in 2029. Based on these data, it can be concluded that this will happen parking shortage on campus in the next five years. As a solution, this research recommends increasing parking capacity through the construction of new parking lots by increasing the number of parking floors on campus. In particular, it is planned to build a multi-storey parking building for motorbikes and additional parking spaces for cars with a more effective and efficient 60° angle parking pattern.